The legal standing of the high prosecutor’s office as a mediator in the resolution of civil disputes between the government and civil society - Poetry, Farahadayune Naharani; Alhadiansyah, Alhadiansyah; Prihatin, Angga; Mangunsong, Putri Tio Octaria; Marpaung, Olyfia Febryanti (Privietlab, 2025)
This study analyzes the legal status and institutional role of the Indonesian Prosecutor’s Office in mediating civil disputes between the government and civil society. Although the Prosecutor’s Office holds a sui generis position under national law—exercising prosecutorial powers alongside authority in civil and administrative matters—its structural placement within the executive branch raises concerns about neutrality and independence. The dual role of the Prosecutor’s Office as both mediator and State Attorney creates an inherent conflict of interest, potentially undermining the neutrality, procedural justice, and equality of arms essential to ADR. Drawing on doctrinal analysis and theories of procedural justice and separation of powers, this study argues that overlapping functions compromise mediation legitimacy. Public trust may decline when mediation is facilitated by an institution aligned with the disputing party. The study recommends limiting the Prosecutor’s Office to consultative functions, while substantive mediation should be handled by independent bodies. Clear functional demarcation and strengthened ethical guidelines are necessary to safeguard neutrality, accountability, and the rule of law.